Preparation of graphene-embedded hydroxypropyl cellulose/chitosan/polyethylene oxide nanofiber membranes as wound dressings with enhanced antibacterial properties - Lin, Che-Min; Chang, Yung-Chi; Cheng, Li-Chang; Liu, Chao-Hsien; Chang, Shin C.; Hsien, Tzu-Yang; Wang, Da-Ming; Hsieh, Hsyue-Jen (Cellulose (London), 2020)
Electrospun nanofiber membranes possess high specific surface area with small pores and thus can be developed as wound dressings for absorbing exudate and also preventing bacterial penetration. In this study, hydroxypropyl cellulose (H), chitosan (C) and polyethylene oxide (P) were chosen as membrane materials to increase the hydrophilicity, anti-bacterial property, and yield of nanofibers, respectively. Additionally, graphene (G) was added to enhance the anti-bacterial property of the membranes. As indicated by SEM, the HCP and HCPG solutions (containing H:4.5 wt%, C:4.5 wt%, P:0.75 wt%, without/with G:0.5 wt%) could be electrospun into HCP and HCPG nanofiber membranes with good fiber morphology using a non-toxic solvent system. Further, the membranes were crosslinked by glutaraldehyde vapor to improve the strength. The tensile strength of the membranes was 1.38–1.82 MPa with a swelling ratio up to 1330–1410%. The water vapor transmission rate (WVTR) of wet HCPG membrane was about 3100 g/m 2 -day, close to the recommended WVTR of wound dressings. The anti-bacterial properties of the membranes were confirmed using three tests against Escherichia coli (Gram-negative bacterium) and Staphylococcus aureus (Gram-positive bacterium). Highly hydrophilic HCP and HCPG membranes prevented the bacterial adherence. The presence of the membranes (especially graphene-embedded HCPG membrane) also greatly reduced bacterial growth. The small pore sizes of HCP and HCPG nanofiber membranes prevented the bacterial penetration to cause infection. Taken together, the HCP and HCPG nanofiber membranes possessed good mechanical properties, appropriate WVTR and high water absorption thus suitable for absorbing wound exudate. Besides, the membranes exhibited nontoxic, anti-fibroblast adhesion and anti-bacterial properties. Therefore, HCP and HCPG nanofiber membranes have the potential to become superior anti-bacterial wound dressings. Graphic abstract